Quantitative magnetic resonance imaging biomarkers in oncological clinical trials: Current techniques and standardization challenges - Jie Deng (KeAi Communications Co., Ltd., 2017)
Radiological imaging plays an important role in oncological trials to provide imaging biomarkers for disease staging, stratifying patients, defining dose setting, and evaluating the safety and efficacy of new candidate drugs and innovative treatment. This paper reviews the techniques of most commonly used quantitative magnetic resonance imaging (qMRI) biomarkers (dynamic contrast enhanced, dynamic susceptibility contrast, and diffusion weighted imaging) and their applications in oncological trials. Challenges of incorporating qMRI biomarkers in oncological trials are discussed including understanding biological mechanisms revealed by MRI biomarkers, consideration of rigorous trial design and standardized implementation of qMRI protocols. Keywords: Quantitative magnetic resonance imaging, Biomarkers, Oncological clinical trials